2015
DOI: 10.1002/humu.22839
|View full text |Cite
|
Sign up to set email alerts
|

NovelCOL2A1Variant (c.619G>A, p.Gly207Arg) Manifesting as a Phenotype Similar to Progressive Pseudorheumatoid Dysplasia and Spondyloepiphyseal Dysplasia, Stanescu Type

Abstract: Progressive pseudorheumatoid dysplasia (PPRD) is a rare, autosomal recessive condition characterized by mild spondyloepiphyseal dysplasia and severe, progressive, early-onset arthritis due to WISP3 mutations. Spondyloepiphyseal dysplasia (SED), Stanescu type, is a vaguely delineated autosomal dominant dysplasia of unknown genetic etiology. Here we report three individuals from two unrelated families with radiological features similar to PPRD and SED, Stanescu type who share the same novel COL2A1 variant and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…It was first reported by Stanescu et al in 1984, and is characterized by painful and progressive narrowing of joint space, platyspondyly, pronounced femoral coxa valga, and normal stature. Jurgens et al reported two probands with SED‐S and suggested that the p.Gly207Arg variant causes a distinct type II collagenopathy with features of progressive pseudorheumatoid dysplasia and SED‐S …”
Section: Resultsmentioning
confidence: 99%
“…It was first reported by Stanescu et al in 1984, and is characterized by painful and progressive narrowing of joint space, platyspondyly, pronounced femoral coxa valga, and normal stature. Jurgens et al reported two probands with SED‐S and suggested that the p.Gly207Arg variant causes a distinct type II collagenopathy with features of progressive pseudorheumatoid dysplasia and SED‐S …”
Section: Resultsmentioning
confidence: 99%
“…The ensuing papers in this special issue of Human Mutation define many of the individual matchmaker services already connected [Buske, et al., a; Chatzimichali et al., ; Sobreira et al., ), or intending to connect to the federated network [Lancaster et al., 2015; Kirkpatrick et al., ; Lambertson et al., ; Mungall et al., ], as well as other core components [Buske et al., b] and concepts [Akle et al., ; Krawitz et al, ] that support genomic matchmaking. A few case examples of discoveries already made through use of matchmaking approaches are highlighted to add further support for this robust approach to rare disease gene discovery [Au et al., ; Jurgens et al., ; Loucks et al., ]. It is our hope that the success of the MME will serve as a model and foundation for innovative data sharing that leverages the increasing role of computational infrastructure to support the scaling of genomics as we collectively advance medicine and improve human health.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic lethality during organogenesis before E15, embryonic growth arrest at E11.5-E12 (Schnieke et al, 1983;Harbers et al, 1984) II (G) Spondyloepiphyseal dysplasias (Lee et al, 1989;Tiller et al, 1990;Chan et al, 1993;Jurgens et al, 2015;Barat-Houari et al, 2016) (G) Spondyloepimetaphyseal dysplasias (Tiller et al, 1995;Sulko et al, 2005) (G) Achondrogenesis 2 (Vissing et al, 1989;Mortier et al, 1995Mortier et al, , 2000Körkkö et al, 2000;Chan et al, 1995;Barat-Houari et al, 2016) (G) Legg-Calvé-Perthes disease (Miyamoto et al, 2007) (G) Kniest dysplasia (Wilkin et al, 1994;Winterpacht et al, 1996) (G) Avascular necrosis of femoral head (Liu et al, 2005;Kannu et al, 2011) Platyspondylic lethal skeletal dysplasia, Torrance type (Nishimura et al, 2004;Zankl et al, 2005) Spondyloperipheral dysplasia (Zankl et al, 2005;Nishimura et al, 2004) (G) Stickler syndrome 1 (Richards et al, 2000(Richards et al, , 2010McAlinden et al, 2008;Körkkö et al, 1993;Barat-Houari et al, 2016) (N) Osteoarthritis with mild chondrodysplasia (Ala-Kokko et al, 1990) (N) Czech dysplasia (Williams et al, 1993;Tzschach et al, 2008;Matsui et al, 2009;Barat-Houari et al, 2016) Perinatal lethality, abnormal skeleton, abnormal cranium, abnormal respiratory system (Li et al, 1995a). IIA isoform-specific knockout: prenatal lethality, holoprosencephal loss of head tissue...…”
Section: Introductionmentioning
confidence: 99%